Realization of Maxim Flouting to Create Humour in Incredibles 2 - Aristyanti, Yullia Ayu; Sutopo, Djoko; Yuliasri, Issy (Universitas Negeri Semarang, 2020)
This study focuses on the analysis of humour creations based on the Grice’s cooperative maxim flouting. It applies descriptive qualitative study where we examined the utterances in Incredibles 2 were flouted to create humour. The results of the study showed that (1) There were 7 kinds of humour created from 19 flouting of quality maxims. (2) There were also 7 kinds of humour created from 45 flouting of quantity maxims. (3) There were only 9 kinds of humour created from 57 flouting of manner maxims. (4) On the flouting of relation maxims, all 11 humour categories were fulfilled from 59 flouting of relation maxims. Furthermore, it is suggested that through the occurance of maxim flouting in the movie especially animation genre which is addressed to the audience gives the knowledge about conversational implicatures. With regard to the creation of humour, it is suggested that the humour is not only a deviation of the cooperative principle and its maxims. Other theory of pragmatics can also be used to analyze the humour such as, politeness principle and also the acts of speech acts.